THE GREAT MOSQUE OF SURAKARTA UPPER STRUCTURE DESIGN - Regine Fortunata, Deithya
Indonesia, a predominantly Muslim country, has the need of a mosque as a place of worship. Today, there are various mosque architectural designs to support comfort in worship. It is a challenge for civil engineer to build a strong, secure, and comfortable mosque structures. The Great Mosque of Surakarta is itended to be built for its purpose. The structure itself consists of 2 stories with a distant gap between columns. The material component is reinforced concrete for the main structure and structural steel on the roof frame structure. The designed structure is classified as seismic design category D which is designed with special moment frame method. The purposes of this thesis are to create structural model based on the reference architectural plan, analyze the structural behavior, provide dimension of concrete structure with the detail of reinforcement for each componen of the main structure, and checks the capacity of steel structure elements with the detail of steel joints for roof frame structure. On the planning, structure is designed for earthquake resistant building. At the end of the design process, the writer can conclude that The Great Mosque of Surakarta has met the design criteria and ready to built based on the specification and methods used.